The Role of Endoplasmic Reticulum Stress Response in Liver Regeneration - Deshmukh, Kshitij; Apte, Udayan (Seminars in Liver Disease, 2023)
Exposure to hepatotoxic chemicals is involved in liver disease–related morbidity and mortality worldwide. The liver responds to damage by triggering compensatory hepatic regeneration. Physical agent or chemical-induced liver damage disrupts hepatocyte proteostasis, including endoplasmic reticulum (ER) homeostasis. Post–liver injury ER experiences a homeostatic imbalance, followed by active ER stress response signaling. Activated ER stress response causes selective upregulation of stress response genes and downregulation of many hepatocyte genes. Acetaminophen overdose, carbon tetrachloride, acute and chronic alcohol exposure, and physical injury activate the ER stress response, but details about the cellular consequences of the ER stress response on liver regeneration remain unclear. The current data indicate that inhibiting the ER stress response after partial hepatectomy–induced liver damage promotes liver regeneration, whereas inhibiting the ER stress response after chemical-induced hepatotoxicity impairs liver regeneration. This review summarizes key findings and emphasizes the knowledge gaps in the role of ER stress in injury and regeneration.
Keywords: liver regeneration; ER stress response; unfolded protein response; liver injury; chemical-induced liver injury; partial hepatectomy